Elderly perception of the repercussions of the COVID-19 pandemic on their health (Research, Society and Development, 2021)
The COVID-19 pandemic indicates a higher mortality rate among the elderly. The study aimed to characterize the perception of the elderly regarding the influence of the pandemic on their own health. This is a survey with a quantitative approach that used the form of the Google Forms platform as a data collection instrument from March to May 2021. 123 elderly people from Brazil participated. For the analysis, descriptive statistics were used, calculating the absolute and relative frequencies. The research followed the ethical criteria of Resolution No. 510/2016. The results describe the participation of elderly people with a mean age of 69 years, female, among other sociodemographic data. Regarding the impact of the pandemic on health in general, 74% reported not having been affected by COVID-19, those who had to be hospitalized, most had comorbidities such as diabetes mellitus and systemic arterial hypertension. Of those who did not have COVID-19, 26% of them reported that they added medication to their routine. Regarding the changes in routine due to the pandemic, their perception is that the COVID-19 pandemic has changed little, they consider that they have not become more dependent, but that there was a change in the routine with social isolation, including health care. A relevant theme was the prevalence of elderly people expressing the feeling of fear, especially the fear of losing a loved one. Despite everything, this period allowed for new learning. It is concluded that the influences of the COVID-19 pandemic are mainly related to feelings of fear, social isolation, self-medication, but also to learning.